New mimic of relapse or regional lymph node metastasis in a cancer survivor: a case of mRNA COVID-19 vaccine-induced lymphadenitis with high FDG uptake. Issue 1 (2nd January 2022) - Tsumura, Yusuke; Asakura, Koiku; Takahashi, Ikuko; Akaihata, Mitsuko; Takahashi, Yoshiyuki; Ishida, Yuji
Abstract: Western countries that were first to administer the COVID-19 vaccination report cases of vaccine-induced axillary lymphadenitis with high FDG uptake. However, no such findings have been reported from any Asian countries. We report here a confusing case of a 31-year-old female cancer survivor with high FDG uptake in her axillary lymph nodes, suggesting recurrence, following mRNA COVID-19 vaccination. Although the value of SUVmax was elevated (12.7), additional imaging revealed that her lymphatic lesions were benign, and they resolved spontaneously. This case of a strong immune reaction to COVID-19 vaccination in regional lymph nodes is the first reported in a Japanese patient. We should be aware of this new mimic and optimize diagnostic imaging methods accordingly in the era of COVID-19.